The value of radiographs in the management of the fractured nose. Issue 4 (December 1993) - Nigam, A; Goni, A; Benjamin, A; Dasgupta, A R
Abstract : Over a 6-month period a record was kept of all patients presenting to the accident and emergency (A&E) department with nasal injuries. The results of the nasal radiographs were analysed to gauge their benefit. It was found that there was poor correlation between the radiological findings and the presence of external deformity, the latter determining the decision to carry out treatment. Routine radiographs of the nose are unnecessary in patients with nasal trauma.